Primary Nocardia Infection in Brain Cerebellum and Brain Stem a Case Report - Akyıldız, Elif Ülker; Öz, Büge; Pakiş, Işıl (The Bulletin of Legal Medicine, 2002)
Nocardia is an anaerobic, gram positive, filamantous microorganism which tends to affect the lungs, brain and skin. Central nervous system infection usually spread from lung via blood flow but primary cerebral nocardia infection is very rare. We report a primary central nervous system nocardiasis without extracranial focus. Key words: Nocardia, infection, central nervous system